A new species of Suphisellus Crotch, 1873 (Coleoptera: Noteridae) from “Los Llanos”, Venezuela - García, Mauricio; Benetti, Cesar João; Camacho, Jesús (Zootaxa, 2012)
Suphisellus shorti sp. n. is described from “Los Llanos”, Venezuela, which brings to six the number of species includedin the Noteridae genus Suphisellus Crotch, 1873 recorded in this country. Specimens were collected in The Plains regionin Venezuela (Apure and Guarico states) using either a light trap or a net. Description and illustration of the new speciesare provided along with a discussion of its systematic position. The new species can be distinguished from the other spe-cies of the genus by the following main characters: crease at posterolateral angle of pronotum weakly marked; numerous setae covering entire surface of prosternal process and medial part of prosternum; shape of male genitalia.